The vascular plants of Iowa : an annotated checklist and natural history - Eilers, Lawrence J. (Bur oak original., 1994)
Anyone who works with the vascular plants of Iowa - researchers, conservationists, teachers, agricultural specialists, horticulturists, gardeners, and so on - and those who are simply interested in knowing more about the state's plants have long felt a need for a comprehensive flora of Iowa. This meticulously researched volume is a giant first step toward such a flora. This book consists of an extended essay on the natural history of the vascular plants of Iowa, a discussion of their origins, a description of the state's natural regions, and a painstakingly annotated checklist o.